Perspectives on My Career in Organic Geochemistry. Issue 1 (5th May 2021) - Meyers, Philip A.
Abstract: I have had the pleasure of studying the organic geochemistry of sediments of lakes and oceans for 50 years. I have especially enjoyed the versatility of organic geochemistry; it can be applied to studies of many kinds of geological sequences and parts of geological time. As an important part of my career, I sailed as a shipboard organic geochemist on seven ocean‐drilling cruises that recovered organic carbon‐rich Cretaceous black shales, Mediterranean sapropels, and upwelling zone sediments. Because most marine sediments contain less than one‐tenth of a percent of organic carbon, learning more about the properties and the paleoceanographic processes important to the formation of these carbon‐rich deep‐sea sequences has been a long‐term theme of my career. At the same time, I have studied organic geochemical records in lakes, where higher sedimentation rates and greater organic carbon concentrations enable higher resolution investigation of depositional processes than in the oceans. In addition, I have studied peat sequences, which provide relatively detailed records of the paleoclimatic histories of their locations. In summary, my scientific curiosity has permitted me to be a paleoceanographer, a paleolimnologist, a paleoclimatologist, and above all an organic geochemist. Plain Language Summary: I have always been curious about the world and how it works, and I have been fortunate to have had a career that has enabled me to pursue these interests. My studies of the organic geochemical properties of sediment sequences in ocean basins, lakes, and peatlands have taken me to many parts of the world, and they have resulted in my collaborating with many interesting and stimulating scientists. My path to this career was meandering. The major steps were discovering that a profession in studying the ocean existed while recovering a hydrogen bomb in southern Spain, to being hired to teach oceanography in Michigan, to participating in deep‐sea drilling cruises, and to chance encounters with scientists who invited me to work with them on lake sediments and peat sequences around the world. A common element through this meandering path has been me being open to opportunities, which is a part of my natural curiosity.